The Agile Legal Management Framework: Bridging Legal and Technology Gaps in Corporate Affairs - Sibongile Gobile,; Olanrewaju Awoyemi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The dynamic corporate environment necessitates that legal departments adapt to rapidly evolving regulatory landscapes and technological advancements. Traditional legal management models, characterized by rigid structures and manual processes, often struggle to keep pace with these changes, leading to inefficiencies, compliance risks, and delays. The Agile Legal Management Framework presents a solution by incorporating agile methodologies and technology-driven innovations into legal processes, bridging the gap between legal functions and technology in corporate affairs. This review emphasizes cross-functional collaboration, iterative workflows, and the integration of legal technology, such as artificial intelligence (AI), automation, and blockchain. By leveraging AI for contract review, legal research, and risk analysis, companies can reduce manual labor, minimize errors, and accelerate decision-making. Blockchain technology provides secure, transparent contract management through smart contracts that automate agreement execution and compliance. This also promotes real-time regulatory monitoring, ensuring companies stay ahead of compliance requirements. Agile project management techniques, such as Scrum and Kanban, are introduced to legal operations, allowing for flexible, continuous improvement and faster response times to legal issues. This adaptability enables legal teams to collaborate more effectively with other departments, fostering a more integrated approach to corporate governance and strategy. While the review offers significant benefits, such as enhanced operational efficiency, cost savings, and better compliance, challenges remain in areas like change management, cultural resistance, and the complexity of technology integration. Thisoutlines how the Agile Legal Management Framework can transform legal departments, enabling them to meet the demands of modern corporate affairs while laying the foundation for ongoing innovation and improvement.
Keywords: Agile; Legal Management; Corporate Affairs; Technology; Review